2021
DOI: 10.1016/j.pediatrneurol.2020.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessments and Interventions for Spasticity in Infants With or at High Risk for Cerebral Palsy: A Systematic Review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In this review, the authors observed several adverse effects, including muscle weakness, injection site pain, bruising, and vomiting. 78 Bonikowski and Sławek conducted a non-systematic review to compare the safety and efficacy of Botox ® , Xeomin ® , and Dysport ® , taking into consideration their pre-administration preparation. These treatments were safe and efficacious against both upper and lower limb hypertonia.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, the authors observed several adverse effects, including muscle weakness, injection site pain, bruising, and vomiting. 78 Bonikowski and Sławek conducted a non-systematic review to compare the safety and efficacy of Botox ® , Xeomin ® , and Dysport ® , taking into consideration their pre-administration preparation. These treatments were safe and efficacious against both upper and lower limb hypertonia.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past twenty years, several systematic reviews in multiple domains of impairment associated with CP [73] beyond the motor component of activity limitations have been published. They range from daily living activities (feeding, sleeping) [74,75] to the senses (hearing, vision) [76,77] to child and family wellbeing and environment (pain, spasticity and tone management, orthotics, parent mental health and parenting) [78][79][80] and developmental functions (communication, cognition) [81].…”
Section: The Why Of Early Detection For Cp: Early Interventionmentioning
confidence: 99%
“…Efficient, inexpensive, remotely accessible, and engaging are some of the highlighted characteristics sought after in the development of novel physiotherapy interventions, particularly in children living in low clinical resources/access and remote areas [13][14][15][16]. The development of such interventions has been further emphasised since the recent COVID-19 pandemic, which interrupted non-essential rehabilitation services including those focusing on patients with CP and imposed mobility restrictions (lockdowns) [17]. An alternative to meet the aforementioned demands is the use low-cost technological tools and exergames to deliver telerehabilitation (TR) interventions.…”
Section: Introductionmentioning
confidence: 99%